Thank you so much for your answer.
I tried to do another thing:
First: To substitute by x'[t]
and x''[t]
in ode2
in terms of ode1
:
x'[t] := Sqrt[2 (a''[t]/a[t] + a'[t]/a[t]^2)]
x''[t] := D[x'[t], t]
Then
ode2 = x''[t] + 3 a'[t]/a[t] x'[t] + v[t] == 0
Gives:
Out[18]= (1-E^(-((Sqrt[2/3] x[t])/mp)))^2 v0+(3 Sqrt[2] (a^\[Prime])[t] Sqrt[(a^\[Prime])[t]/a[t]^2+(a^\[Prime]\[Prime])[t]/a[t]])/a[t]+(-((2 (a^\[Prime])[t]^2)/a[t]^3)+(a^\[Prime]\[Prime])[t]/a[t]^2-((a^\[Prime])[t] (a^\[Prime]\[Prime])[t])/a[t]^2+(a^(3))[t]/a[t])/(Sqrt[2] Sqrt[(a^\[Prime])[t]/a[t]^2+(a^\[Prime]\[Prime])[t]/a[t]])==0
But now there is in ode2, x[t]
which comes from v(t)
.. So how to integrate ode1:
x'[t] := Sqrt[2 (a''[t]/a[t] + a'[t]/a[t]^2)]
To get x[t]
Then solve ode2 as a third order differential equation in a'''[t]
.